2023
DOI: 10.1038/s41598-023-28493-4
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of a single Arg$$_9$$ peptide across a DOPC/DOPG(4:1) model membrane using the weighted ensemble method

Abstract: It is difficult to observe a spontaneous translocation of cell-penetrating peptides(CPPs) within a short time scale (e.g., a few hundred ns) in all-atom molecular dynamics(MD) simulations because the time required for the translocation of usual CPPs is on the order of minutes or so. In this work, we report a spontaneous translocation of a single Arg$$_9$$ 9 (R9) across a DOPC/DOPG(4:1) model membrane within an order … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The dynamic GUV leakage assays serve as an effective method to monitor real-time membrane permeabilization and deformation caused by active molecules, which are commonly employed for investigating molecule–membrane interactions. , GUVs composed of DOPC, DOPG (at a mol ratio of 4:1; previously utilized , ) and labeled with 1 mol % RhB-PE were prepared using the conventional electro-forming method and immobilized on a glass substrate through biotin–streptavidin binding. Calcein, a water-soluble and membrane-impermeable fluorophore, was introduced into the solution for evaluating membrane permeability.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic GUV leakage assays serve as an effective method to monitor real-time membrane permeabilization and deformation caused by active molecules, which are commonly employed for investigating molecule–membrane interactions. , GUVs composed of DOPC, DOPG (at a mol ratio of 4:1; previously utilized , ) and labeled with 1 mol % RhB-PE were prepared using the conventional electro-forming method and immobilized on a glass substrate through biotin–streptavidin binding. Calcein, a water-soluble and membrane-impermeable fluorophore, was introduced into the solution for evaluating membrane permeability.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, CPP showed various translocation mechanisms: Arg9 seems to translocate through a transient pore formation [69,70], a mechanism shared by DynA WT. On the other hand, DynA L5S and TP2 may involve direct translocation (through a quick and transient pore or without pore formation) of a monomeric peptide, leading to a minimum leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and computational studies of other arginine-containing peptides have shown that trans-leaflet flip-flop can be induced by peptide membrane insertion. 41,42 If NAF-1 44−67 induces trans-leaflet flip-flop, a cooperative insertion enhancement could occur when an inner leaflet > outer leaflet anionic lipid gradient is present. For example, if the outer leaflet and inner leaflet are 30 and 50 mol % PA, respectively, permeating NAF-1 44−67 could flip some PA lipids to the OL.…”
mentioning
confidence: 99%
“…In an unperturbed bilayer, the time scale of lipid flip-flop is very slow, on the order of hours to days with a large ∼20–30 kcal mol –1 free energy barrier. However, when NAF-1 44–67 forms a membrane defect, this barrier may be reduced, neutralizing any gradient between the leaflets. Experimental and computational studies of other arginine-containing peptides have shown that trans-leaflet flip-flop can be induced by peptide membrane insertion. , If NAF-1 44–67 induces trans-leaflet flip-flop, a cooperative insertion enhancement could occur when an inner leaflet > outer leaflet anionic lipid gradient is present. For example, if the outer leaflet and inner leaflet are 30 and 50 mol % PA, respectively, permeating NAF-1 44–67 could flip some PA lipids to the OL.…”
mentioning
confidence: 99%